PENGARUH INTERNALISASI NILAI-NILAI SERVIAM MELALUI PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK TERHADAP KARAKTER DAN PRESTASI PESERTA DIDIK - Karinna Karinna; Aripin Tambunan (Lembaga Penelitian STKIP Widya Yuwana, 2026)
This research was conducted with the aim of examining the influence of the internalization of serviam values through Catholic religious education learning on the character and academic achievement of students at SMP Santa Ursula Jakarta. The research data were obtained from the distribution of questionnaires to 71 students from grade VIII at SMP Santa Ursula Jakarta. The data were analyzed using SmartPLS. This research employed a quantitative approach with analytical methods to identify the coefficient influence of the research variables. A portion of the population was used to collect data for this research. The results of the Multivariate Analysis of Variance (MANOVA) test show that the significance values for the four multivariate tests; Pillai’s Trace, Wilks’ Lambda, Hotelling’s Trace, and Roy’s Largest Root, on the Intercept variable yielded a significance value of 0.000 (p < 0.05). This indicates that the overall model is significant. Furthermore, for the independent variable of serviam values, the four multivariate tests also produced significance values smaller than 0.05, with details as follows: Pillai’s Trace: F = 2.653; Sig. = 0.018; Wilks’ Lambda: F = 2.686; Sig. = 0.017; Hotelling’s Trace: F = 2.717; Sig. = 0.016; Roy’s Largest Root: F = 4.722; Sig. = 0.005. These results demonstrate a significant influence of serviam values on students’ character and academic achievement.